2020
DOI: 10.1111/jcmm.14940
|View full text |Cite
|
Sign up to set email alerts
|

A novel inhibitory role of microRNA‐224 in particulate matter 2.5‐induced asthmatic mice by inhibiting TLR2

Abstract: Epidemiological studies have shown that elevated concentrations of particulate matter 2.5 (PM2.5) correlate with increased incidence of asthma. Studies have highlighted the implication of microRNAs (miRNAs) in asthmatic response. Here, the objective of this study is to explore the effect of miR‐224 on PM2.5‐induced asthmatic mice. Ovalbumin (OVA) was utilized to establish asthmatic mouse models, which were then exposed to PM2.5, followed by miR‐224 expression detection. Next, lesions and collagen deposition ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“… 52 Moreover, miR-224 suppresses airway epithelial cell inflammation in PM2.5-induced asthmatic mice due to its ability in reducing the expression of pro-inflammatory mediators transforming growth factor-β (TGF-β), MMP9, TIMP-1, and RORγt. 53 These reports highlighted the protection from inflammation conferred by miR-224. Concordantly, present findings of reduced levels of TNF-α, IL-1β, and IL-6 suggest an anti-inflammatory action of miR-224-3p in the alleviation of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“… 52 Moreover, miR-224 suppresses airway epithelial cell inflammation in PM2.5-induced asthmatic mice due to its ability in reducing the expression of pro-inflammatory mediators transforming growth factor-β (TGF-β), MMP9, TIMP-1, and RORγt. 53 These reports highlighted the protection from inflammation conferred by miR-224. Concordantly, present findings of reduced levels of TNF-α, IL-1β, and IL-6 suggest an anti-inflammatory action of miR-224-3p in the alleviation of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…MMP9 is a proinflammatory molecule involved in extracellular matrix (ECM) remodeling via degradation of ECM molecules. Work by this group and others have also reported increases in the expression of MMPs following exposure to PM [ 5 , 29 , 30 ]. The observed increase in levels of RAGE in this and several previous studies could be linked with MMP9 upregulation [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 95%
“…Zhang et al demonstrated that when HBE cells are exposed to PM2.5, miR-382-5p triggers lung in ammation through the targeting relationship with CXCL12 49 . Li et al showed that overexpression of miR-224 inhibited the airway epithelial cell in ammation and airway remodeling induced by PM 2.5 in asthmatic mice by reducing the expression of TLR2 50 . However, more in-depth studies are needed on the potential biological mechanisms between exposure to air pollutants and miRNA, exploring the role of miRNA in PM 2.5 between normal and cancer cells.…”
Section: Discussionmentioning
confidence: 99%